Dynamics of changes of cellular composition of the centre of focus of inflammation in secondary chronic inflammation during treatment with glyukozaminilmuramildipeptid - Shevchenko, A. N.; Bibichenko, V. A. (Journal of Education, Health and Sport, 2017)
In experiments on rats was showed that the essential infiltration is observed in the secondary chronic inflammation during treatment with glyukozaminilmuramildipeptid in the early periods, which leads to an increase of the efficiency of phlogogen elimination. In connection with this, the further course of inflammation decreases, which is accompanied by a decrease of subsequent infiltration. The use of glyukozaminilmuramildipeptid also stimulates the accumulation of macrophages, tissue basophils, fibroblasts in the initial periods of inflammation, which contributes to more pronounced repair in the acute period of inflammation and a decrease in the development of connective tissue in the period of pronounced chronization of the process.